Implementasi Dan Hambatan Kebijakan Liberalisasi Pendidikan Tinggi Di Indonesia - Ferdiansyah R (Department of International Relations, Universitas Andalas)
Liberalization of higher education often gets rejection from the people in developing countries. It is considered as part of commodification of education. This also happens in Indonesia. This paper attempts to answer the question why liberalization of higher education in Indonesia cannot run fast? There are three things to be explained. First, it explains the conditions of international political structure that affects Indonesia’s education policy. Second, it elaborates how the process of making and implementing the policy are carried on. Third, it discusses how the public responses the policy. This research shows that liberalization of higher education in Indonesia has given rise to many opposition movements, which then lead to ambiguities in Indonesia commitments to liberalize the higher education. Keywords: GATS, Liberalization, Higher Education, WTO, Globalization